Exports and FDI motivations: empirical evidence from US foreign subsidiaries - Chiara Franco (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
The expected indirect benefits Foreign Direct Investments (FDI) are supposed to bring into the host countries are drawn mainly from studies at the microeconomic level. Empirical analyses examine whether FDI may be the source of productivity spillover effect on local firms and a new emerging literature analyses the effect with regard to the their export performance. However, conclusive results have not been reached so far. Two main shortcomings affect this literature: firstly, it is difficult to generalize results valid across countries; secondly, the role played by FDI motivations is largely disregarded. For these reasons, the aim of the paper is that of testing the effects of US FDI on export intensity at the sectoral level in 16 OECD countries over the period 1990-2001. Through these data, we are able to disentangle asset seeking and asset exploiting motivations and especially we are able to distinguish the channels through which the effect is going to occur. The findings show that taking into consideration the different motivations for which Multinational Enterprises (MNEs) invest abroad is relevant. The asset exploiting motivations, and in particular market seeking FDI, are those that affect export intensity to a greater extent.
Keywords: F14; F21; F23; 330